Femicide in Greek-Cypriot and Turkish-Cypriot communities in Cyprus: A pilot study - Kouta, Christiana; Kofou, Elina; Zorba, Akile (My University, 2019)
Purpose: The aim of this article is to discuss a pilot study on femicide in Greek-Cypriot and Turkish-Cypriot communities in Cyprus. Methods: A quantitative methodology was used to gather data from the police between 2010 and 2016 for the Greek-Cypriot community on women and girls who have been killed and where the perpetrator charged, alleged or convicted is a man. Also, qualitative methodology was used, gathering media reports for both communities between 2010 and 2017. Results: Twenty-eight and twelve femicide cases were identified in the Greek and Turkish Cypriot communities respectively. Most of the victims were killed by their husbands or boyfriends often at their home. It seems that masculine viewpoint was dominant in the media representations of these cases. Conclusions: Femicide prevention is in its early stages in Cyprus. It seems that a preventative and interventional strategy is needed to reduce the number of women killed by men.
Keywords: Femicide; Greek-Cypriot; Turkish-Cypriot; Bi-communal